SAT0254 Immunohistological analysis of chondrocytes in facet joints from anklyosing spondylitis patients. (23rd January 2014) - Bleil, J.; Syrbe, U.; Maier, R.; Sieper, J.; Appel, H.
Abstract : Background: Beside inflammation new bone formation and ankylosis are a major issue in patients with ankylosing spondylitis (AS). The mechanisms leading to new bone formation and ankylosis in AS are still purely understood. Objectives: We have undertaken a histopathological analysis of chondrocytes and cartilage from facet joints of AS patients and compared the results to osteoarthritis (OA) patients and controls in order to analyze mechanisms of new bone formation and ankylosis in diarthrodial joints. Methods: Facet joints from 15 AS, 12 OA patients and 8 controls (autopsies without spinal diseases) were analyzed. Immunohistochemistry was performed to detect different biomarkers indicating anabolic (Collagen II, Collagen X, beta-Catenin, Sox9, Runx2) or catabolic/anti-anabolic (sclerostin, MMP3, MMP13) processes in the cartilage. Areas of interest were defined by alcian blue staining. All chondrocytes-of the entire joint space were counted including a subanalysis of three regions: (1) superficial zone; (2) proliferating zone; (3) tidemark. Results: The staining results and statistical analysis are summarized in table 1 . The percentage of biomarker positive cells is shown. The subanalysis of the different cartilage regions revealed that in the tidemark (region3) AS- (p=0, 006) and OA-patients (p=0, 0008) displayed significantly more Runx2+cells than controls. In AS patients collagen X+ chondrocytes were mainly observed again in region 3 and in the cartilage of already ankylosed facet joints. Conclusions: Several anabolic and catabolic factors are clearly less expressed in chondrocytes from AS patients compared to OA and are rather close to the findings in controls. Interestingly, sclerostin was significantly lower expressed in AS patients compared to OA and controls while Collagen II was significantly higher expressed in AS in comparison to the OA patients and controls, possibly indicating that chondrocytes seem to play a major role in repair mechanisms in AS. Disclosure of Interest: None Declared